The Habitat of the Nascent Chicxulub Crater. Issue 4 (24th November 2020) - Bralower, T. J.; Cosmidis, J.; Fantle, M. S.; Lowery, C. M.; Passey, B. H.; Gulick, S. P. S.; Morgan, J. V.; Vajda, V.; Whalen, M. T.; Wittmann, A.; Artemieva, N.; Farley, K.; et al.
Abstract: An expanded sedimentary section provides an opportunity to elucidate conditions in the nascent Chicxulub crater during the hours to millennia after the Cretaceous‐Paleogene (K‐Pg) boundary impact. The sediments were deposited by tsunami followed by seiche waves as energy in the crater declined, culminating in a thin hemipelagic marlstone unit that contains atmospheric fallout. Seiche deposits are predominantly composed of calcite formed by decarbonation of the target limestone during impact followed by carbonation in the water column. Temperatures recorded by clumped isotopes of these carbonates are in excess of 70°C, with heat likely derived from the central impact melt pool. Yet, despite the turbidity and heat, waters within the nascent crater basin soon became a viable habitat for a remarkably diverse cross section of the food chain. The earliest seiche layers deposited with days or weeks of the impact contain earliest Danian nannoplankton and dinocyst survivors. The hemipelagic marlstone representing the subsequent years to a few millennia contains a nearly monogeneric calcareous dinoflagellate resting cyst assemblage suggesting deteriorating environmental conditions, with one interpretation involving low light levels in the impact aftermath. At the same horizon, microbial fossils indicate a thriving bacterial community and unique phosphatic fossils including appendages of pelagic crustaceans, coprolites and bacteria‐tunneled fish bone, suggesting that this rapid recovery of the base of the food chain may have supported the survival of larger, higher trophic‐level organisms. The extraordinarily diverse fossil assemblage indicates that the crater was a unique habitat in the immediate impact aftermath, possibly as a result of heat and nutrients supplied by hydrothermal activity. Plain Language Summary: The newly formed Chicxulub crater was rapidly filled by seawater then disturbed by tsunami and seiche waves. Sedimentary layers deposited as wave energy declined provide a unique window into the environment of the nascent crater in the months and years to millennia after the impact. Geochemical data show temperatures in hotter regions of the crater in excess of 70°C for the first few years with heat derived from the underlying melt sheet via hydrothermal circulation. Cooler regions of the crater became habitats soon after impact with a suite of fossils indicating diverse life on the seafloor and sea surface, ranging from microbes to marine arthropods, and possibly fish. We suggest that this community was sustained by nutrients and heat from the hydrothermal system. The rapid early recovery in the Chicxulub crater and ocean above demonstrates the resiliency of life under extraordinarily harsh conditions, which has important ramifications for early life on Earth and life on other planets. Key Points: Sediments derived from decarbonation of the Chicxulub impact target were deposited by tsunami and seiche waves over months to years followed by a layer with atmospheric fallout Temperatures in the ocean above the hotter regions of the crater were in excess of 70°C, with heat likely derived from the central impact melt pool Cooler regions within the crater basin became habitats soon after impact with diverse life ranging from microbes to marine arthropods, and possibly fish